A potential electric vehicle curriculum development argument in Malaysia based on database analysis: a review - Basri, Azizul Qayyum; MD Yasir, Ahmad Shah Hizam; Awang Zainal, Awangku Zaini; Peng, Jin; Nik Mohamed, Nik Mohd Zuki; Abdul Raj, Mohd Nazri; Nelfiyanti, N.; Othman, Muhammad Azri (Cogent Education, 2025)
A study of electric vehicle (EV) education is essential for its implementation in a country. The researchers analyzed databases on EV education studies accredited by mandatory journal platform from 2004 to 2024. Based on the findings, up to 42 prior studies may be linked to EV teaching strategies. The purpose of the study is to determine how to create an EV education-based curriculum that centers on four research concerns. According to the data analysis results, Research Cluster 2 (RC2), Research and Development (R&D), and Project-Based Learning (PBL) are the most commonly used research methodologies in the past (RQ1); there are differences between ‘developed’ and ‘developing’ countries concerning the policy, finance, teachers, knowledge, facilities, and students’ preparedness for multidisciplinary studies (RQ2); graduate degrees in electrical, mechanical, and mechatronic engineering are a suitable educational level to be integrated with EV education (RQ3). The researchers will analyze the findings of this study to determine the most effective strategy for EV education in developing country (RQ4). Lastly, the researchers discuss various constraints and potential directions to advance suitable EV education in ‘developing countries’ like Malaysia